The Colonized Reading of Historic Colombian Constitutions. Historical Examples and Methodological Proposal - Botero Bernal, Andrés (História do Direito, 2025)
this paper exposes certain practices of academic colonization in the way constitutional history has been done, both by legal historians and constitutionalists. This text argues, with concrete examples, that every time a new fashionable transnational theory appears, the way in which Colombian constitutions of the past are viewed is altered, which has prevented a correct and decolonized reading of our own constitutional history.